Light‐Activated Decellularized Extracellular Matrix‐Based Bioinks for Volumetric Tissue Analogs at the Centimeter Scale (Adv. Funct. Mater. 32/2021). (10th August 2021) - Kim, Hyeonji; Kang, Byeongmin; Cui, Xiaolin; Lee, Se‐Hwan; Lee, Kwangseok; Cho, Dong‐Woo; Hwang, Woonbong; Woodfield, Tim B. F.; Lim, Khoon S.; Jang, Jinah
Abstract : Extracellular Matrix‐Based Bioinks In article number 2011252, Khoon S. Lim, Jinah Jang, and co‐workers present a novel visible‐light activated tissue‐derived bioink that can fabricate clinically relevant volumetric tissue analogs on a centimeter scale. These bioinks enable print complex structures with increased shape fidelity, improved printing versatility, and even excellent tissue regenerative capacity. These advantages of the light‐activated bioinks open new avenues for the biofabrication of soft tissues applicable in regenerative medicine.